Microsoft Azure security infrastructure - Diogenes, Yuri; Shinder, Thomas W.; Shinder, Debra Littlejohn (Microsoft Press, 2016)
Implement maximum control, security, and compliance processes in Azure cloud environments In Microsoft Azure Security Infrastructure, three leading experts show how to plan, deploy, and operate Microsoft Azure with outstanding levels of control, security, and compliance. You'll learn how to prepare infrastructure with Microsoft's integrated tools, prebuilt templates, and managed services - and use these to help safely build and manage any enterprise, mobile, web, or Internet of Things (IoT) system. The authors guide you through enforcing, managing, and verifying robust security at physical, network, host, application, and data layers. You'll learn best practices for security-aware deployment, operational management, threat mitigation, and continuous improvement - so you can help protect all your data, make services resilient to attack, and stay in control no matter how your cloud systems evolve. Three Microsoft Azure experts show you how to: Understand cloud security boundaries and responsibilities; Plan for compliance, risk management, identity/access management, operational security, and endpoint and data protection; Explore Azure's defense-in-depth security architecture; Use Azure network security patterns and best practices; Help safeguard data via encryption, storage redundancy, rights management, database security, and storage security; Help protect virtual machines with Microsoft Antimalware for Azure Cloud Services and Virtual Machines; Use the Microsoft Azure Key Vault service to help secure cryptographic keys and other confidential information; Monitor and help protect Azure and on-premises resources with Azure Security Center and Operations Management Suite; Effectively model threats and plan protection for IoT systems; Use Azure security tools for operations, incident response, and forensic investigation.